Combustion characteristics, kinetics and thermodynamics of Pinus Sylvestris pine needle via non-isothermal thermogravimetry coupled with model-free and model-fitting methods. (December 2020) - Chen, Ruiyu; Li, Quanwei; Xu, Xiaokang; Zhang, Dongdong; Hao, Ronglin
Abstract: The combustion characteristics of Pinus Sylvestris pine needle are studied employing thermogravimetric analysis in air. Kinetic and thermodynamic analyses are performed using two model-free methods and one model-fitting method. Results indicate that two peaks and two shoulders occur in the variations of reaction rate with conversion rate. The maximum and average values of reaction rate decrease with heating rate. The combustion process can be divided into three stages with the thresholds of conversion rate α = 0.15 and 0.75. The average values of activation energy/pre-exponential factor for stage 1 (0 = α ≤ 0.15), stage 2 (0.15 < α < 0.75), stage 3 (0.75 = α ≤ 1) and the entire combustion process are 163.18 kJ/mol/9.55 × 10 9 min -1, 166.46 kJ/mol/2.13 × 10 9 min -1, 132.09 kJ/mol/5.67 × 10 6 min -1 and 156.89 kJ/mol/3.89 × 10 9 min -1, respectively. The reaction model characterizing stage 1, 2 and 3 is A1/3, A1/4 and F3, respectively. The obtained kinetic parameters can be used to acceptably predict the conversion rate data. The variations of the change in enthalpy (Δ H ), Gibbs free energy (Δ G ) and entropy (Δ S ) with α indicate that more favorable reactions occur and more homogeneous or well-ordered products are generated with the progressing of combustion. Besides, the average values of Δ H, Δ G and Δ S vary little with heating rate. Highlights: Two peaks and two shoulders occur in the reaction rate curves. Three stages may be divided in the combustion of Pinus Sylvestris pine needle. Model-free and model-fitting methods are used for kinetic modeling. Validation of the obtained kinetic parameters is conducted. Thermodynamic parameters are obtained and analyzed.